A coupled CFD model for an accurate and fast prediction of the unsteady operation process of a proton exchange membrane fuel cell. (15th November 2022) - Wang, Min; Xu, Liangfei; Yang, Xiaofan
Graphical abstract: Highlights: A coupled model is proposed for accurate and fast prediction of a PEM fuel cell performance. For the 1D model, fuel cell is simplified to several branch circuits which is in a parallel mode. Influence of the output voltage on the fuel cell performance is investigated in detail. Evolution of the current density, concentration and membrane water content are analyzed. Abstract: A proton exchange membrane (PEM) fuel cell is one of the highly efficient hydrogen utilization devices. However, due to the complex physical and chemical processes in fuel cells, developing a mathematical model of the PEM fuel cell is challenging. In this study, a new coupled model based on the computational fluid dynamics method and a 1D model is proposed for the accurate and fast prediction of PEM fuel cell performance. First of all, the proposed model is validated using the literature data. It is then applied to simulate the distribution and evolution of the current density, hydrogen and oxygen mass fraction, and membrane water content in catalyst layer (CL). Results show that the increase in the current density is attributed to the increase in the consumption rate of hydrogen and oxygen and the increase in the membrane water content. In addition, the stabilized supply of the oxygen in cathode and the membrane water content in the anode CL are critical for the improvement of the fuel cell performance. For the cases studied in this research, when the output voltage decreases from 0.6 V to 0.3 V, the current density increases from 5738.1 A/m 2 to 15171.2 A/m 2 . The average oxygen mass fraction in the cathode CL and the average membrane water content in the anode CL decreased by 42.3 % and 9.6 %, respectively. In addition, when the fuel cell starts up at 0.6 V, the concentration of hydrogen and oxygen drops gradually decreases along the flow direction of the CL, while the membrane water content rapidly increases initially, and then increases slowly, with the turning point around at approximately 2.2 × 10 -3 m. Under the combined effect of hydrogen and oxygen concentration, as well as the membrane water content, the current density first increases and then decreases, with the maximum value exceeding 6500 A/m 2 .